Combined effect of Metformin and Pitavastatin on blood glucose in Alloxan induced diabetic rats - Jahan, Sarwat; Begum, Zinnat Ara; Afrin, Syeda Fahmida; Shefin, Sultana Marufa; Khatun, Siddika; Jahan, Qazi Alifa (Bangladesh Journal of Medical Science, 2025)
Background Comparing to general population, the diabetic population is at higher risk of cardiovascular disease. Therefore, along with glycemic control in diabetic patient control of other risk factors for cardiovascular problem is also important. metformin is widely used oral hypoglycemic agent and pitavastatin as an antilipidemic agent. Combination of antidiabetic and hypolipidemic drug has been suggested as a rich source for treatment. Objective The current study focused on the efficacy of Metformin, Pitavastatin and their combinations. Materials and methods 48 healthy male Wister strains of albino rats weighting to 180- 220gm aged between 10-12wks were selected for the study. The experimental condition was all set in a very. Alloxan was prepared accordingly. The metformin and pitavastatin solution were prepared every 48hrs to maintain its activity. Data were analyzed using ANOVA in each variable. Result Blood glucose level in all six groups after two weeks treatment on day 15, the mean value and its Standard Deviation of fasting blood glucose level in Metformin treated group was (9.37±0.92 mmol/L) which is significant. Whereas the mean ± SD of fasting blood glucose level in Pitavastatin treated group was (13.81 ±1.31mmol/L) not significant. When given in combination Metformin and Pitavastatin these mean ± SD of fasting blood glucose levels mean were (6.93 ±0.84mmol/L) and (5.21±0.93) in Metformin 100 mg and Pitavastatin 2mg treated group and Metformin 200 mg and Pitavastatin 4 mg respectively, which were even reduced more and show highly significant than the Metformin treated group rats. Conclusion Combination of Metformin and Pitavastatin is able to improve glucose level more than that in single drug therapy BJMS, Vol. 24 No. 04 October’25 Page : 1146-1152